HERMENEUTIKA DOUBLE MOVEMENT FAZLUR RAHMAN DAN SIGNIFIKANSINYA TERHADAP PENAFSIRAN KONTEKSTUAL AL-QUR’AN - Muhammad Labib Syauqi (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
Using hermeneutics as a method of contextual interpretation has begun to be massive in Indonesia, although its compatibility is still debatable. The double movement hermeneutics initiated by Fazlur Rahman is one of the methods widely adopted by Indonesian Muslim scholars in their research. This study tries to investigate the extent to which Fazlur Rahman's theory of double movement influences the development of contextual interpretation theory in Indonesia. This article uses the library research method by operationalizing the historical theory of Kuntowijoyo's thought in order to understand the development of thought more comprehensively. This study concludes that Rahman's double movement hermeneutics provides the basis for the emergence of contextual interpretation theories in Indonesia, such as The Ma'nā cum Maghzā theory and The Tafsīr Maqāshidī theory. The last two theories combine hermeneutics with the Ulūmul Qur'ān and Maqāsid Syarī’ah to formulate a contextual interpretation in Indonesia.